Modern trends in unemployment (MCIT: Proceedings of International scientific and practical conference, 2021)
Unemployment is an integral part of a market economy. This means that the inevitable feature of a market economy is the existence of a certain level of unemployment, despite the fact that unemployment is one of the visible indicators of macroeconomic instability in the country. Unemployment causes macroeconomic instability precisely when the level of actual unemployment exceeds the set natural limit.
Keywords: market economy, visible indicators, macroeconomic instability, employment services